Illustrations and studies in Neotropical Orchidaceae. 6. The Lepanthes guatemalensis group (Pleurothallidinae) in Costa Rica - Pupulin, Franco (2014)
We revise and characterize the group of species close to Lepanthes guatemalensis. The group comprises eight species in Costa Rica. Three new species are described and illustrated. Lepanthes durikäensis is distinguished by the non resupinate flowers, the lateral sepals ovate with the apical tails diverging, the lower lobe of petals lanceolate-subfalcate, up-curved and the pinkish column. Lepanthes leporina is recognized by the resupinate flowers with yellow sepals, faintly suffused with red, the petals violet, the lip orange, the bifid synsepal with the apices of the lateral sepals not forming tails, the lateral sepals subequal to the dorsal sepal, the petals markedly convex with the upper lobe elliptic-lanceolate and the lobes of the lip connivent at apex. Lepanthes sanctiorum is characterized by the small plants less than 1.1 cm tall, the short peduncle less than 10 mm long, the petals as wide as the lip length and the blades of the lip distinctly diverging at apex. All the species are described and illustrated on the basis of Costa Rican material. A key to the species of the group is provided